2015
DOI: 10.1007/s10096-015-2495-6
|View full text |Cite
|
Sign up to set email alerts
|

COPD patients with ventilator-associated pneumonia: implications for management

Abstract: Data on the occurrence and outcome of patients with chronic obstructive pulmonary disease (COPD) and ventilator-associated pneumonia (VAP) are quite limited. The aim of this study was to determine if COPD intensive care unit (ICU) patients have a higher rate of VAP development, different microbiological aetiology or have worse outcomes than other patients without VAP. A secondary analysis of a large prospective, observational study conducted in 27 European ICUs was carried out. Trauma patients were excluded. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 41 publications
3
40
1
2
Order By: Relevance
“…However, antibiotic treatment is well-known risk factor for late-onset ICU-acquired infections, and MDR bacteria emergence [22]. Our results contradict several earlier studies that identified COPD as an independent risk factor for VAP [7,8], but are in line with data from a recent retrospective analysis of a large prospective observational study conducted in 27 European ICUs and including 2082 intubated patients, which reported a similar 20% incidence of VAP among COPD and non COPD patients [9].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, antibiotic treatment is well-known risk factor for late-onset ICU-acquired infections, and MDR bacteria emergence [22]. Our results contradict several earlier studies that identified COPD as an independent risk factor for VAP [7,8], but are in line with data from a recent retrospective analysis of a large prospective observational study conducted in 27 European ICUs and including 2082 intubated patients, which reported a similar 20% incidence of VAP among COPD and non COPD patients [9].…”
Section: Discussionsupporting
confidence: 77%
“…Among intubated COPD patients, VAP incidence widely ranges, from 6 to 34% [7][8][9]11], possibly because of different VAP diagnostic criteria used in these studies. The relatively low rate of VAP among COPD patients, together with the lack of significant difference with non-COPD patients, may be due to the significantly higher previous exposure to antibiotics in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ABC is a common cause of ICU-acquired pneumonia, accounting for 8 to 14% of VAP in the United States 50 and Europe, 51 but much higher rates (19% to >50%) in Asia, 48,52 Latin America, 53 and some Middle Eastern 54 countries. In the United States, rates of VAP due to ABC increased from 4% in 1986 to 7.0% in 2003; no increase was observed for any other gram-negative bacilli.…”
Section: Hospital-acquired Pneumoniamentioning
confidence: 99%
“…50 In a study of 411 cases of VAP from nine European countries, A. baumannii was implicated in 13.9% of cases. 51 In a cohort of 827 cases of VAP in 27 ICUs in Europe, A. baumannii was implicated in 11% of early-onset and 26.5% of late-onset VAP. 56 In Greece and Turkey, ABC was the most common cause of VAP.…”
Section: Hospital-acquired Pneumoniamentioning
confidence: 99%